In Ovo and Oral Administration of Probiotic Lactobacilli Modulate Cell- and Antibody-Mediated Immune Responses in Newly Hatched Chicks - Alizadeh, Mohammadali; Bavananthasivam, Jegarubee; Shojadoost, Bahram; Astill, Jake; Taha-Abdelaziz, Khaled; Alqazlan, Nadiyah; Boodhoo, Nitish; Shoja Doost, Janan; Sharif, Shayan (Frontiers in Immunology, 2021)
There is some evidence that lactobacilli can strengthen the immune system of chickens. This study evaluated the effects of in ovo and oral administration of a lactobacilli cocktail on cytokine gene expression, antibody-mediated immune responses, and spleen cellularity in chickens. Lactobacilli were administered either in ovo at embryonic day 18, orally at days 1, 7, 14, 21, and 28 post-hatches, or a combination of both in ovo and post-hatch inoculation. On day 5 and 10 post-hatch, spleen and bursa of Fabricius were collected for gene expression and cell composition analysis. On days 14 and 21 post-hatch, birds were immunized with sheep red blood cells (SRBC) and keyhole limpet hemocyanin (KLH), and sera were collected on days 7, 14, and 21 post-primary immunization. Birds that received lactobacilli (107 CFU) via in ovo followed by weekly oral administration showed a greater immune response by enhancing antibody responses, increasing the percentage of CD4+ and CD4+CD25+ T cells in the spleen and upregulating the expression of interferon (IFN)-α, IFN-β, interleukin (IL)-8, IL-13, and IL-18 in the spleen and expression of IFN-γ, IL-2, IL-6, IL-8, IL-12, and IL-18 in the bursa. These findings suggest that pre-and post-hatch administration of lactobacilli can modulate the immune response in newly hatched chickens.